Oral cholera vaccine - Rosli, Rozita; Shamsudin, Mariana Nor; Abdullah, Syahrilnizam; Nograles, Nadine; Hanafi, Aimi Melati (2013)
The present invention provides s DNA plasmid pVAX1 comprising coding sequences of the Vibrio cholerae genes ctxB, optionally encapsulated in alginate or cellulose acetate phthalate microspheres. This plasmid is suitable as the active ingredient for an oral vaccine against cholera.